2017
DOI: 10.1016/j.jacc.2017.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Lifestyle Intervention in Patients With Coronary Artery Disease

Abstract: Among patients with coronary artery disease, nurse-coordinated referral to a comprehensive set of community-based, widely available lifestyle interventions, with optional partner participation, leads to significant improvements in LRFs. (RESPONSE-2: Randomised Evaluation of Secondary Prevention by Outpatient Nurse SpEcialists 2; NTR3937).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 28 publications
2
84
0
3
Order By: Relevance
“…Another interesting finding came from the RESPONSE‐2 (Randomised Evaluation of Secondary Prevention by Outpatient Nurse Specialists 2) study, which studied the impact of a nurse‐coordinated referral to community‐based lifestyle programs to control smoking, overweight, and physical inactivity. Participation of patient's partners was associated with a significantly greater success rate 133. Thus, regular face‐to‐face contacts with specialized nurses and physicians in combination with telemonitoring systems and the inclusion of partners might help translate the proven health benefits of rehabilitation programs into long‐standing lifestyle changes and improved prognoses.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting finding came from the RESPONSE‐2 (Randomised Evaluation of Secondary Prevention by Outpatient Nurse Specialists 2) study, which studied the impact of a nurse‐coordinated referral to community‐based lifestyle programs to control smoking, overweight, and physical inactivity. Participation of patient's partners was associated with a significantly greater success rate 133. Thus, regular face‐to‐face contacts with specialized nurses and physicians in combination with telemonitoring systems and the inclusion of partners might help translate the proven health benefits of rehabilitation programs into long‐standing lifestyle changes and improved prognoses.…”
Section: Perspectivesmentioning
confidence: 99%
“…Participation of patient's partners was associated with a significantly greater success rate. 133 Thus, regular face-to-face contacts with specialized nurses and physicians in combination with telemonitoring systems and the inclusion of partners might help translate the proven health benefits of rehabilitation programs into long-standing lifestyle changes and improved prognoses.…”
Section: Perspectivesmentioning
confidence: 99%
“…Secondary prevention programs, with particular emphasis on intensive lifestyle modification including weight reduction and smoking cessation, have been proven to be beneficial among patients with coronary artery disease (CAD) . Although recent studies showed adequately treated lifestyle factors were associated with success rates of catheter ablation, significant gaps still exist in the understanding of the definition of treatment targets for the individual risk factors in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the COURAGE study, after 5 years, the proportion of patients who smoked was only reduced from 23% to 19%, the proportion of patients who engaged in physical activity increased from 58% to 66% and body mass index (BMI) increased from 28.8% to 29.3 kg/m 2. The best results were obtained in the recent RESPONSE‐2 study, in which intervention led to a significant improvement in lifestyles (37% in the case group vs 26% in control group), and in the Nurses' Health Study and Health Professionals Follow‐up Study, in which there was a total mortality reduction of 17% …”
Section: Discussionmentioning
confidence: 99%
“…30 Even in the COURAGE study, after 5 years, the proportion of patients who smoked was only reduced from 23% to 19%, the proportion of patients who engaged in physical activity increased from 58% to 66% and body mass index (BMI) increased from 28.8% to 29.3 kg/m 2. 31 The best results were obtained in the recent RESPONSE-2 study, in which intervention led to a significant improvement in lifestyles (37% in the case group vs 26% in control group), 32 34 However, it should be stressed that if risky lifestyle factors persist (especially cigarette smoking), the residual risk remains high despite treatment with statins. 35 Revascularization improves the quality of life by reducing symptoms in patients who have recurrent chest pain despite optimal medical therapy but does not reduce either the risk of heart attack or the risk of death.…”
Section: Methodsmentioning
confidence: 99%